Legal protection of the coastal environment and beach areas In light of Law No. 02-02 - Bouguendoura, Slimane; Atik, Nadira (Journal of Human Sciences, 2023)
The great importance of the coastal environment and beach areas, in various areas of life, whether social, economic, tourism, even cultural and historical, is evident in legal protection at the international level, and at the internal level in various Algerian laws, including Law No. 02- 02 on the protection and valorization of the coast, in order to maintain the ecological balance at the waterfront level within the framework of sustainable development, respect coastal reconstruction tools, whether residential areas or industrial and tourist areas, and to achieve a balanced living environment for all living creatures and the various components of coastal nature, vegetation and economic activities worthy of protection, within the framework of balancing between Development and environmental requirements ?.this is what must be researched because it is a very important subject, and the authors neglected it, due to lack of knowledge of its various aspects that deserve study by analyzing the relevant texts.